Problem Based Learning’s Effect in Understanding of Idioms Found on Agatha Christine's Novel at SMAN 1 Onanrunggu - Octavianna, yessy octavianna; Pakpahan, Jelita; Sidabutar, Usman (Eduscape : Journal of Education Insight, 2024)
The aims of this study are to assess student achievement in reading comprehension through the implementation of the problem-based learning (PBL) method and to determine whether this method has a significant impact on students’ achievements in understanding of idioms founds on Agatha Christine’s novel for 11th grade in SMA N 1 Onanrunggu. The research used experimental-quantitative design with the population is 11th grade students at SMA N 1 Onanrunggu, with has five parallel classes and total the students are 145. Two classes were selected as samples, namely XI MIPA 1 and XII MIPA 2, where XI MIPA 2 became a group of experiments taught using the problem based learning method, while XI Mipa 1 became a control group taught by the conventional method. The data collection used a double-choice test and data analysis used the t-test. The results of the study showed that there was an increase in student values from pre-test to post-test in the experimental group. Statistical analysis shows that t-observed values are greater than t-table values (2.5 > 2,000) at the significance level of 0.05. This indicates that the zero hypothesis (Ho) is rejected and the alternative hypotheses (Ha) are accepted. Thus, it can be concluded that the use of problem-based learning methods has a significant influence on student performance in reading comprehension. This conclusion confirms the positive and significant impact of the use of problem-based learning methods in the context of the reading comprehension of eleventh grade of SMA N 1 Onanrunggu.